An economical regimen of human diploid cell strain anti-rabies vaccine for post-exposure prophylaxis. - Warrell, M; Warrell, D; Suntharasamai, P; Viravan, C; Sinhaseni, A; Udomsakdi, D; Phanfung, R; Xueref, C; Vincent-Falquet, J; Nicholson, K; Bunnag, D; Harinasuta, T (1983)
Vaccine regimens using 0.1 ml human diploid cell strain vaccine (HDCSV) given intradermally (id) in single and multiple sites, or with aluminum hydroxide adjuvant given subcutaneously (sc), were compared with the regimens of HDCSV and Semple vaccine currently suggested by WHO. Some groups were also given human rabies-immune globulin (HRIG). Neutralising antibody titres were monitored for 3 months. Antibody was detected earliest in subjects given 0.1 ml HDCSV id at each of eight sites. The highest antibody titres from day 14 onwards were found after intramuscular (im) administration of HDCSV, but the multiple-site id regimen, which requires only one quarter of the volume of vaccine required for the im regimen, gave similar results, provided that a booster was given on day 91. This finding suggests that a treatment schedule based on this regimen would be suitable for post-exposure prophylaxis. Adjuvanted vaccine gave similar results to the same amount of antigen given id. Semple vaccine produced the lowest titres. HRIG, given at the high dose of 40 IU per kg, suppressed the antibody response to some of the regimens.